2009
DOI: 10.1111/j.1744-1617.2009.01278.x
|View full text |Cite
|
Sign up to set email alerts
|

Where Is the Justice? Parental Experiences of the Canadian Justice System in Cases of Child Sexual Abuse*

Abstract: Research concerning child victims of sexual abuse in the judicial system cites largely negative experiences and outcomes. However, few investigations focus on parental experiences of the justice system. Using a grounded theory method this Canadian study explored parental experiences of legal and judicial processes for child sexual abuse victims. Nineteen in‐depth interviews with parents encountering the justice system, as well as interviews with professionals working in those systems were analyzed. Results sho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 34 publications
0
6
0
Order By: Relevance
“…This may have been either because they did not engage with the criminal justice system or because the lengthy delays in prosecuting crimes in Ireland meant that these parents were still at an early stage in that process. Other studies have highlighted how parents have felt abandoned and unsupported by the criminal justice system (Alaggia, Lambert, & Regehr, 2009; Eastwood & Patton, 2002). The practice of police questioning children who report abuse was described by parents in this study as traumatizing, and in some cases, children and their parents interpreted this approach by the police as implying that the child had done something wrong.…”
Section: Discussionmentioning
confidence: 99%
“…This may have been either because they did not engage with the criminal justice system or because the lengthy delays in prosecuting crimes in Ireland meant that these parents were still at an early stage in that process. Other studies have highlighted how parents have felt abandoned and unsupported by the criminal justice system (Alaggia, Lambert, & Regehr, 2009; Eastwood & Patton, 2002). The practice of police questioning children who report abuse was described by parents in this study as traumatizing, and in some cases, children and their parents interpreted this approach by the police as implying that the child had done something wrong.…”
Section: Discussionmentioning
confidence: 99%
“…The executive is always powerful, thus, there is always the need of an arm like the judiciary to regulate its behaviors including its temptation to abuse office, violate human rights, neglect the promulgation of laws; and allocation of the required resources. Notwithstanding, the executive and the legislature can enact and assent to laws but if the judiciary is not effectively delivering justice by interpreting the laws, the life and living conditions of the powerless in particular, will be more at risk since they can't be spared any abuse and violation by perpetrators knowing they wouldn't be punished for it, exponentially increasing crimes and public insecurity (Adler, 2015) concurring with: in seeking justice for their abuse children, parents have realized the following unpleasant issues within the legal system vis-à-vis the welfare of their loved children: losing control of everything, lot of inconsistencies, children treated like adults, dissatisfaction with courts' outcomes; and instead of getting some therapeutic benefits children are systematically re-abuse (Alaggia, Lambert, & Regehr, 2009). In view of the degree and complexity of child sexual abuse, for the law to have positive impacts, it is critical that transformative justice is given a chance where applicable(GenerationFive, 2017).…”
Section: Ineffective Judiciary Systemmentioning
confidence: 99%
“…Essentially lengthy court proceedings discourage children and parents to seek justice, and justice delayed is justice denied (Rass-Masson & Rouas, 2017). Thus, it is critical that in the process of ensuring justice is delivered, the special needs of the disadvantaged including children is seriously pondered otherwise it becomes re-abusive sessions in addition to justice denied concurring with: in many instances, parents pursuing justice for their sexually abused children reported that the judicial reforms in some jurisdictions don't yield the desired results since some of the children have complained been traumatized and re-abuse for the second time by the harsh court proceedings (Alaggia et al, 2009). To ensure children enjoy the right to access justice, the current legal systems of some jurisdictions must be changed so that they will be able to offer fair, supportive; and secured child sensitive proceedings (Back, 2012).…”
Section: Lengthy and Intimidating Court Proceduresmentioning
confidence: 99%
“…So, it has become probably one of the most important things that we have. (ID 101) Although researchers have begun to address the potentially traumatic impact of trials more broadly (Edwards and Miller, 2019;Leclerc et al, 2020;Lonergan et al, 2016;McQuiston et al, 2019), and the impact of involvement in the justice system for victims of sexual violence (Englebrecht, 2012;Kunst et al, 2015;Regehr et al, 2008;Spencer et al, 2018) and their families (Alaggia et al, 2009), to date little work has specifically addressed the unprecedented growth in graphic digital evidence and its potentially traumatic impact on survivors, victims and families.…”
Section: The Ubiquity Of Video Evidencementioning
confidence: 99%
“…While the primary victim is the individual upon whom acts of sexual violence were perpetrated, the impacts often radiate to others who care for them, sometimes referred to as secondary victims (Alaggia et al, 2009). This is particularly true in situations in which the primary victim is a minor, or when the acts of violence culminate in murder.…”
Section: Loved Onesmentioning
confidence: 99%